Foliar trichomes of Croton section Barhamia (Euphorbiaceae) - Martínez Gordillo, Martha; Espinosa Matías, Silvia (Instituto de Ecología, A.C., 2005)
Trichomes on both leaf surfaces of 17 species of section Barhamia genus Croton were studied using scanning electron microscopy. Stellate-rotate, lepidote-stellate, multiradiate and dendritic trichomes as well as embedded epidermal glands were observed. Based on the morphological variations observed in the section, Barhamia cannot be characterized indisputably by features of the trichomes, although at the species level, trichomes serve as useful distinguishing features.